The Effectiveness of Implementing a Closed-list Proportional System in Selecting Legislative Members from the Perspective of Islamic Law - Priyanto, Ari; Satria Alamsyah, Mirah; Yasin Al Arif, M. (KnE Social Sciences, 2024)
The legislative elections using an open-list proportional system always generate identical controversies during general election season. This, mainly involves the prevalence of misconduct by both the prospective legislative candidates themselves and their campaign teams. This issue has become a latent problem in every general election season, resulting in several adverse effects, including high campaign costs leading to corruption practices and poor political education to the public. The closed proportional system is once again considered as a solution to prevent vote-buying practices, also known as money politics. This research is a normative legal study using the statute approach, conceptual approach, and case approach. There are two types of legal materials used in this research. First, primary legal materials, namely Law No. 2 of 2011 Regarding Amendments to the Political Parties Law and Law No. 7 of 2017 Regarding General Elections. This study focuses on the importance of reconsidering the implementation of the closed proportional system in legislative elections as an effort to prevent the ongoing issue of money politics, which has been a latent problem in every general election in Indonesia. This research aims to reevaluate the use of the closed proportional system as the most suitable system to combat money politics practices. Keywords: money politics, legislative elections, proportional system